Two new species of Darnini (Hemiptera: Membracidae) from Colombia and Peru - Gonzalez-Mozo, Laura; Mckamey, Stuart; Ware, Jessica L.; Hamilton, George (Zootaxa, 2017)
Two new species of treehoppers (Hemiptera: Membracidae) from Colombia and Peru are described. Cyphotes colombiensis sp. nov. and Hypheodana sakakibarai sp. nov. both belong in the tribe Darnini. New distribution records are provided for Cyphotes (from Colombia) and Hypheodana (from Peru).